UNDERSTANDING AUTONOMOUS SENSORY MERIDIAN RESPONSE (ASMR) AND A STUDY ON FOOD AS A SENSORY TRIGGER: FOOD FOR SENSES - SREESHA S,; RAJASEKHARAN, ARJUN; Pai , Gita R. (International Journal of Psychosocial Rehabilitation, 2020)
People perceive and appreciate food in a manner that is multisensory, where information from the different senses is integrated at both the perceptual and semantic levels in order to give rise to specific multisensory experiences. There are various factors that play a major role in modulating the diner’s overall experience. Visual cues such as color and texture have been shown to exert a significant influence on the perceived flavor and acceptance of foods. Techniques typically belonging to the realm of painting and visual communication design have been theorized to be a useful and resourceful tool when it comes to designing food experiences. The food acts as a meditation for the body and mind. This is where we are introduced to Autonomous Sensory Meridian Response (ASMR). ASMR as a known phenomenon has only been active in the online community, where it is widely popularized by YouTube. The paper tries to demonstrate that food is not just to satisfy hunger but serve as a major part in human psyche by helping in relieving our stress; and also highlights on the misconception of food television sprinkling sexual innuendoes. The culinary ingredients in the food are in the fashion of art and that would transform the diner’s presumption and their experience of food. Our senses are vital to our ability to function physically, mentally, spiritually and socially. The connection between aesthetics and our senses is so profound that one could not exist without the other. In this paper, it is our intention to analyze and discuss the cause and effect of portraying food consumption among people who process sensory information in an atypical manner by the application of Aesthetics theory.